Interleukin-8 upregulates integrin β3 expression and promotes estrogen receptor-negative breast cancer cell invasion by activating the PI3K/Akt/NF-κB pathway. Issue 2 (10th August 2015) - Shao, Nan; Lu, Zhenhai; Zhang, Yunjian; Wang, Mian; Li, Wen; Hu, Ziye; Wang, Shenming; Lin, Ying
Highlights Integrin β3 and IL-8 expression was inversely correlated with ER status in breast cancer. IL-8 siRNA decreased the invasion and integrin β3 expression in breast cancer cells. IL-8 siRNA attenuated the phosphorylation of PI3K and Akt. IL-8 siRNA inhibited NF-κB transcriptional activity.